Larangan Homoseksual Studi Analisis Tafsir Maqashidi Pada QS. Al-A’raf [7]: 80-81 - Ahmad Murtaza; Raisa Zuhra Salsabila Awaluddin (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
This article discusses the story of the Prophet Luth QS. Al-A’raf [7]: 80-81 by using the maqashidi interpretation method which was initiated by Abdul Mustaqim. The commentators agree to prohibit homosexual behavior that has been practiced by the people of the Prophet Luth. Although they have various reasonsfor prohibiting it, if you read it as a whole, the opinion of the commentators leads that homosexuality has violated the nature of human beings who live in pairs between women and men. However, using Maqashdi Tafsir is not only limited to prohibiting homosexuals which is limited by the meaning of the text but also results in the meaning behind the QS. Al-A’raf [7]: 80-81 when viewed from the maqashid, namely hifz al-din, hifz nasl, hifz al-‘aql, and hifz nafs, there is no benefit in homosexual behavior except for actions that go beyond the limits and has violated human nature.